Gambaran Tingkat Pengetahuan Mahasiswa Keperawatan Universitas Advent Indonesia Tentang Bantuan Hidup Dasar - Kurniawan, Samuel; Tambunan, Evelyn Hemme (Innovative: Journal Of Social Science Research, 2024)
An emergency is a situation where a person requires fast, precise and responsive treatment to prevent disability or death. Inappropriate actions can worsen the condition and increase the risk of disability and death. Therefore, an integrated and effective service system is needed in handling emergency patients or victims. As prospective medical personnel, nursing students need to master knowledge about Basic Life Support (BHD) to provide appropriate assistance in emergency conditions. This study aims to evaluate the level of knowledge of Indonesian Adventist University Nursing students about BHD. The research design used was descriptive quantitative with a cross-sectional approach, involving level III and IV students. Research was conducted at Indonesian Adventist University to assess students' level of knowledge regarding BHD in emergency situations. The results of the analysis show that the majority of students have a good level of knowledge, with 62 people (82.5%) in the good category, 13 people (17.3%) sufficient, and no one has insufficient knowledge. The knowledge category is determined based on an ordinal scale, with a score of 76-100% for the good category, 51-75% for sufficient, and ≤ 50% for poor. Overall, level III and IV Nursing students at Indonesian Adventist University have a good understanding of BHD, with a percentage of 71.2%. Keywords: Basic Life Support, Emergency, Level of Knowledge